Modeling and analysis of a district heating system containing thermal storage - Akkaya, Berna Melissa; Romanchenko, Dmytro (My University, 2013)
The need for space heating and hot water in the residential and services sector makes up a major part of the total Swedish energy demand. This need is to a large extent satisfied by district heating (DH). In the future, it is expected that the energy system will include a larger share of intermittent renewable energy sources. This is likely to result in more fluctuating supply of electricity and hence, more volatile electricity prices. The presence of thermal storage (TS) can increase the flexibility of the DH system in terms of mitigating imbalances between demand and supply. It could also imply a substantial economic value if electricity price becomes more variable. The aim of this master thesis project is to increase the understanding of rational operational strategy in DH systems and assess the value of the TS in present and future perspectives. For this reason a techno-economic computer-based model, along with four scenarios, has been developed. A nonlinear mixed integer optimization implemented in the GAMS software. The model analysis is applied to the DH system of Borås. The reference scenario, representing the current DH system of Borås including TS, can be compared to real operational records. In addition, the reference scenario is also analyzed without TS in the system to estimate its value. The second scenario reflects a future with higher volatility in the electricity market price than today. Scenario three investigates the ability of the TS to serve as a redundancy unit while the fourth scenario estimates the most economically beneficial investment alternative in the case of a system expansion or unit replacement. Thus, the first and the third scenarios put emphasis on the TS from a current system perspective whereas the other two provide insights into future prospects. The model results indicate a drop in total system heat production cost when including TS in the DH system. This would also enhance overall efficiencies of the base load units and reduce the number of starts and stops of the peak load boilers. A sensitivity analysis of the minimum allowed TS capacity level showed that there is no incentive for keeping it at low capacity levels. The results based on a possible future price pattern imply that the total heat production costs drops with higher volatility in electricity prices given the presence of combined heat and power (CHP) and TS units. The model results also suggest that the TS could be a sufficient back-up unit in the case of a sudden black out of some of the heat generation capacities. In the case of a DH system expansion it would be environmentally and economically advantageous to invest in a base load production unit.
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Energiteknik; Energy; Basic Sciences; Sustainable Development; Energy Engineering